The Analysis of Marxism in the Movie Jack the Giant Slayer - Badri Akandi; Dwi Taurina Mila Wardhani (Pioneer: Journal of Language and Literature, 2019)
This research was about Marxism in Jack the Giant Slayer on social class and kind of Marxism. Marxism was an important thing in the society because Marxism wanted to remove social classes. Thus, this research was to describe how social classes could influence someone’s roles in the society. This research used descriptive qualitative method. The research was conducted by accommodating two theories: kinds of Marxism by Tyson (2006) and social class by Barry (2002). Tyson’s theory (2006) classifies Marxism into classism, patriotism, religion, rugged individualism, and consumerism. On the other hand, Barry’s theory (2002) classifies social class into the upper class, the middle class, and the lower class. The findings of the analysis reveal that there were ten data in Jack the Giant Slayer. The researcher found ten forms of Marxism, There were one form of classism, twelve forms of rugged individualism, and one form of consumerism. The most of kind dominant Marxism was classism. Besides, the researcher found three forms of social class, they were the upper class, the middle class, and the lower class. There were four characters of the upper class, one character of the middle class, and two characters of the lower class. The dominant social class was the upper class, which appeared in four characters.